Dinamika Mombolasuako di Sulawesi Tenggara: Perspektif Hukum Islam : - Ipandang (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This article examines the dynamics of the mombolasuako that emerge in Coastal Tolaki society of Southeast Sulawesi in the perspective of Islamic law. This dinamics was triggered by actions that come out of the traditions of Coastal Tolaki community. Where this society has a strict marriage tradition by holds fast to the principle of